(untitled) (Research, Society and Development, 2022)
The objective of this study was to review the literature regarding the use of botulinum toxin in the treatment of bruxism. The bruxism, contact static or dynamic of the teeth, at times other than those that occur during normal functions of chewing or swallowing, is always associated with an emotional state changes of the patient, i.e., the stress. This habit parfunctional constitutes one of the most difficult challenges to restorative dentistry and, in some cases, produces reflections in the periodontium, in the masticatory muscles, in the temporomandibular joint. You can also cause headache, behavioral effects and psychological, and it is very difficult to its resolution, depending on the severity of the wear produced. How to treat the Botulinum toxin type A has been used in patients who suffer from erectile dysfunction, because it is a less invasive alternative and which demonstrates good therapeutic results.